Veículo elétrico autônomo para ambiente industrial controlado por gps de baixo custo - Zaro, Eduardo (Universidade do Vale do Rio dos Sinos, 2019)
Companies are increasingly looking for cost reductions in products manufacturing pro cesses, in order to get more profit and be more competitive in the market. The use of robots, automatic systems and AGVs in the industry shows the growth and need of increasingly opti mized processes. The purpose of this project is to develop an autonomous electric vehicle, which can travel through the factory environment of a company, transporting people and supplies. The major advantage of this project is the cost and time reduction it brings to the company - since it is a low cost product when compared to the similar alternatives in the same segment - and the need lessness of user interaction to move the vehicle. The vehicle is 100% electric-powered, being able to travel up to 90km without recharging, making it a cheap alternative to its competitors. The autonomous electric vehicle can travel through both internal (factory) and external (streets and highways) areas, making it a very versatile product, regardless of the condition of the road or path where it operates. To get around, the device uses GPS and compass signals to locate itself in space and follow pre-defined routes across geographic locations. When indoors, it uses infrared sensors, identifying the difference in colors and thus following predefined lines designated on the floor. The vehicle is controlled by microcontrollers, which read and interpret user interactions to make sure the product moves around areas and routes defined by the user with safety, transport ing people and supplies. The key feature of the product is safety: because it shares the space with people, the vehicle has several sensors that perform analysis and avoid collisions and/or accidents. After developing the prototype, it is possible to conclude that the technologies used in au tonomous vehicles are of great importance and provide knowledge to keep improving solutions in this segment. The results show the developed product achieved satisfying performance, but with great room for improvement in the future.
Keywords: Veículo Elétrico Autônomo; GPS - Sistema de Posicionamento Global; AGV; Ambiente Industrial; Automatic Electric Vehicle; GPS - Global Positioning System; Industrial Environment